Invariant three and four-phase equilibria in the Mg-Rich corner of Mg-Cu-Sn ternary system - Vicente, Eduardo E.; Esteban, Adolfo; Bermúdez, S.; Arcondo, B.; Sirkin, H.; Hojvat de Tendler, Ruth (Comisión Nacional de Energía Atómica; Argentina)
Fil: Vicente, Eduardo E. Comisión Nacional de Energía Atómica; Argentina